COMMUNICATION STRATEGY: A CASE STUDY BETWEEN LECTURER AND STUDENTS IN ONLINE ENGLISH COURSE - Irene Brainnita Oktarin; Tyas Desita Wengrum (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2021)
The Covid-19 pandemic is the main reason in doing online learning. The change in this learning process is one of the efforts to stop the spread of the virus. Lecturers and students must adapt with this changes so that the learning process can run well. Many problems that arise in online learning can be solved if the lecturer has good communication strategies and styles during the online learning process. This study aims to analyze and explain some problems that arise in online English course and some communication strategies between lecturer and students to improve the quality of learning. This is a qualitative study with case study method. The subjects of this study were a lecturer and 10 students of the 4th semester Management study program who took English courses. Data collection in this study was done by observation and interview. The result showed that the problems are learning burnout, students’ frustration, and obstacles in providing feedback from students. The communication strategy between lecturers and students during the online courses is very important, such as lecturer should plan the learning process as well as possible and create a creative, varied, and innovative way to foster student enthusiasm in learning, lecturer should apply two-way communication that providing opportunities for students in responding either in the form of questions, discussions, or comments, and implement a collaborative learning system strategy in the form of project based learning (PjBL) and problem based learning (PBL).